Diagnosis of Enteroviral-associated-Meningitis by RT-PCR for the First Time in Iraq - Faiza L. Tuama; Yassen I. Omeran; Manal Khalid Abdul Ridha; Walid K. Ridha (College of Pharmacy / Mustansiriyah University, 2008)
Introduction: A protocol for testing cerebrospinal fluid specimens using RT-PCR for the diagnosis of central nervous system infections was developed 2 and used to test 20 CSF specimens. Objectives: A-Evaluation of efficiency of In-house prepared Extraction reagent. BAmplified of Enteroviral-RNA genome by single-step RT-PCR. Methods: 20 cerebrospinal fluid specimens were included. RNA was extracted from 250μl by method Chomcynki, 1993. EV-RT-PCR was performed for all specimens studied. Results: We successfully isolated total RNA from 20 CSF specimens of AM cases. Ten of 20 specimens were positive by RT-PCR. Conclusions: Single-step extraction method was allowed isolation of RNA in 4hr. and provided both high yield and purity of un-degraded RNA preparation. EV-RTPCR detection test is suitable for clinical diagnosis of EV-related meningitis and may improve the management of EV-related neurologic syndromes.